Yield Maximization of Pigeonpea under Erratic Situation of Climate through Innovative Technology System of Pigeonpea Intensification - Singh, R.K.; Singh, S.R.K.; Gautam, U.S. (Indian Journal of Extension Education, 2018)
The field experiment was conducted at farmer’s field and KVK Instructional farm of Panna district of Madhya Pradesh. Majority of the farmers in this region are still cultivating the traditional practices/ varieties along with higher seed rate without the arrangement of row and plant spacing during kharif season, therefore plant population was not maintained as per recommendation under erratic rainfall, which causes reduced production as well as higher cost of production. Under such circumstance maintaining adequate number of plants by transplanting of young seedling of pigeon pea in presence of both a biotic and biotic stresses. Counter of this problems and exploit full potential through certain crop contingencies including transplanting of pigeon pea seedling in main field so as to maintain adequate plant population for compensating yield loss during Kharif season. Resulted that average higher yield, Net return and cost benefit ration was found in both year 13.9 q/ha, ` 25815, B:C ratio 1:2.0 respectively under transplanting of pigeon pea seedling as compared to farmers practices 9.6 q/ha, ` 15600, B:C ratio 1:1.96 respectively. Farmers responded positively to the results of the demonstration and those who participated in the demonstration trainings were willing to adopt System of Pigeon pea Intensification. And scientist advises to adoption of this module for small and marginal farmers with less land to take advantage of this method can yield dramatic results with less number of seeds and saving of water and nutrients.
Keywords: B:C ratio; Net return transplanting and yield